Guidelines for bachelor's thesis preparation - Krasnokutska, N. S.; Prokhorenko, O. V.; Nashchekina, O. M.; Kovshyk, V. I. (My University, 2022)
This manual is intended to provide guidance for writing a thesis to students pursuing a bachelor degree in Management and studying within the Business Administration or the Management of Organizations and Administration educational programs.
Keywords: guidelines; bachelor’s thesis; academic style of writing; special elements of text; abstract; plagiarism policy